1999
DOI: 10.1583/1074-6218(1999)006<0270:lfoegf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Endoluminal Grafting for Aneurysmal and Occlusive Disease in the Superficial Femoral Artery

Abstract: The prototype ELG used in this series demonstrated durability similar to conventional surgical therapy utilizing synthetic material. Endoluminal grafting of FP lesions may be a more durable alternative to classical bypass once devices and techniques are refined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…At 3 years, these rates had declined to 46% and 68% but were still comparable to conventional surgical therapy using synthetic conduits. 12 Since the majority of our cases involved complex disease patterns with long segments of the SFA occluded, oftentimes proximally, and severe stenosis of the femoral bifurcation, our treatment strategy combined conventional revascularization techniques such as embolectomy and thromboendarterectomy with intraoperative endografting. Moreover, most of our patients had severe symptoms, poor runoff, and simultaneous involvement of the upper popliteal segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 3 years, these rates had declined to 46% and 68% but were still comparable to conventional surgical therapy using synthetic conduits. 12 Since the majority of our cases involved complex disease patterns with long segments of the SFA occluded, oftentimes proximally, and severe stenosis of the femoral bifurcation, our treatment strategy combined conventional revascularization techniques such as embolectomy and thromboendarterectomy with intraoperative endografting. Moreover, most of our patients had severe symptoms, poor runoff, and simultaneous involvement of the upper popliteal segment.…”
Section: Discussionmentioning
confidence: 99%
“…3,[7][8][9] Developments in endovascular grafts, which combine metallic stents with polyester or polytetrafluoroethylene (PTFE) graft material, have the potential to enhance long-term results in the SFA. [10][11][12][13][14][15] We report our initial experience using a PTFEcovered self-expanding endograft in femoropopliteal occlusive disease. …”
mentioning
confidence: 99%
“…3). [77][78][79][80][81][82] However, the early and midterm outcomes with the Hemobahn stent-graft seem to be competitive with prosthetic surgical bypass. 31,[83][84][85][86][87][88][89][90] It should be noted that these are relatively small series of patients, and the utility of ePTFE in TASC C and D disease is unclear.…”
Section: Covered Stentsmentioning
confidence: 99%
“…Early endograft designs deployed in the femoropopliteal arteries have proved to be no more durable than conventional synthetic bypass grafts. 6,7 Rodriguez-Lopez et al, 6 for example, reported a 68% 2-year secondary patency in 51 patients treated with a prototype PTFE endograft with terminal Palmaz stents for fixation. Half the devices occluded in the 36month mean follow-up; 20% of the endografts demonstrated stenoses in the stents, but these were attributed to intimal hyperplasia that began at stent edges unintentionally exposed by slippage of the PTFE material during deployment.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In the ongoing search for a stent-graft design that can achieve long-term patency in small arterial systems, researchers have used a variety of graft materials and metals. Among the fabrics, expanded polytetrafluoroethylene (ePTFE), with its excellent biocompatibility and proven durability, has been used in vascular reconstructions for decades.…”
mentioning
confidence: 99%